EFEKTIVITAS KEBIJAKAN PERCEPATAN PENURUNAN STUNTING DI DESA CISAAT KECAMATAN CICURUG KABUPATEN SUKABUMI - Pujiawanti Puspita Rahayu (Jurnal Dialektika Politik, 2025)
This research is motivated by a problem found during the pre-survey regarding the effectiveness of the policy to accelerate stunting reduction. This study aims to determine how effective the policy for accelerating stunting reduction is in Cisaat Village, Cicurug Sub-district, Sukabumi Regency. Effectiveness is crucial to achieving the established objectives in the policy process. The theory used refers to Campbell J.P's theory (1970) in Mutiarin and Zaenudin (2021:96), which comprises five research dimensions: program success, target achievement, program satisfaction, input and output level, and overall goal achievement. The research approach used in this study is qualitative with a descriptive method. Data collection techniques include interviews, observations, and documentation, applying triangulation techniques. Data analysis involves data reduction, data presentation, and conclusion drawing. Informants were selected using purposive and snowball sampling, resulting in 7 individuals: Village Chief, Village Acceleration Team for Stunting Reduction, Family Planning Field Counselor (PLKB), Village Midwife, Family Assistance Team (TPK), and Families with stunted children. The findings of this research indicate that the policy for accelerating stunting reduction in Cisaat Village, Cicurug Sub-district, Sukabumi Regency, is effectively implemented. This is evident from the following factors: (1) program success in stunting reduction acceleration has been quite successful, (2) target achievement in stunting reduction acceleration has been on the right track, (3) program satisfaction in stunting reduction acceleration has been good, (4) input and output level in stunting reduction acceleration have been optimally implemented, and (5) overall goal achievement in stunting reduction acceleration has been progressing well.